Příklady z matematiky

                          ( x+3)( y+5)  = (x+1)(y+8)

                          (2x-3)(5y+7) = 2(5x-6)(y+1)

                      xy +5x +3y +15 = xy +8x +y +8

             10xy +14x -185y - 21 = 10xy + 10x -12y -12

                                    -3x + 2y = -7  / ( 4)

                                      4x – 3y = 9  / ( 3)

                                   -12x + 8y = -28

                                      12x - 9y = 27

                                                   y = 1

 

x =                   = 3

 

 

L1=( 3+3)(1+5) = 6.6 = 36

P1= (3+1)(1+8) = 4.9 = 36

 

L2= (2.3-3)(5.1+7) = 3.12 =36

P2= 2(5.3-6)(1+1) = 36

 

 

 

                                 P = [ 3;  1 ]